2005
DOI: 10.1021/bp040040x
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Aromatic Compounds Contained in Kraft Mill Effluents Treated by an Aerated Lagoon

Abstract: Kraft mill effluents were biologically treated in an aerated lagoon (AL) (3.4 L) to evaluate the behavior of aromatic compounds by UV-vis spectroscopy. Under aerobic conditions, biological oxygen demand (BOD(5)) removal was between 84% and 95%, whereas soluble chemical oxygen demand (COD(s)) removal ranged between 40% and 60%. A slight increase was observed in the VIS(436)/COD(s) relationship (0.101-0.110), indicating that color reduction was less than the total organic matter reduction expressed by COD(s). Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 18 publications
4
19
0
5
Order By: Relevance
“…These results suggest that the residual COD consisted in lignin compounds, which were also the major aromatic species in these effluents. The same results were found by Chamorro et al (2005) and Milestone et al (2004).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…These results suggest that the residual COD consisted in lignin compounds, which were also the major aromatic species in these effluents. The same results were found by Chamorro et al (2005) and Milestone et al (2004).…”
Section: Resultssupporting
confidence: 88%
“…These results suggest that the residual COD consisted in lignin compounds, which were also the major aromatic species in these effluents. The same results were found by Chamorro et al (2005) and Milestone et al (2004).VIS 400 and VIS 436 show color behavior during the aerobic treatment. Low values show that recalcitrant compounds are present in the treated effluent (Çeçen, 1999; Çeçen, 2003).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…However, as already discussed, there was removal of other organic compounds measured as COD and DOC. The results are similar to the observations reported by Çeçen (1999) and Chamorro et al (2005).…”
Section: Effect On the Absorption Wavelengths In The Uv-vis Spectral supporting
confidence: 92%
“…In order to identify specific groups of compounds based on recent studies reported in the literature (Thomas et al, 1996;Çeçen, 1999;Arslan-Alaton et al, 2002;Langergraber et al, 2004;Chamorro et al, 2005;Lunidquist et al, 2007), a scan was performed of the UV-VIS spectrum between 200 and 346 nm. Çeçen (1999) proposed the use of the following wavelengths and ratios: VIS 346 for lignosulphonic acids; UV 254 for aromatic compounds; UV 280 for lignin derivatives, and the relationships VIS 346 /CODd and UV 280 /CODd.…”
Section: Physicochemical Analysismentioning
confidence: 99%